Numerical analysis of the problem of flow past a cylindrical body applying the r-functions method and the galerkin method - Lamtyugova, S. N.; Sidorov, M. V. (LUBLIN–RZESZOW, 2014)
The article considers the stationary problem of viscous incompressible fluid flow past a cylindrical body. For solving the problem it is proposed a numerical method, based on the joint use of R-functions method and the Galerkin method. The computational experiment has been conducted for the task of flow past square cylinder for different Reynolds numbers.
Keywords: viscous incompressible fluid; the Galerkin method; flow problem; the R-functions method